Coronary artery dissection by an oversized balloon. (4th December 2014) - Yafi, Wael; Jacquemin, Laurent
Abstract : Percutaneous coronary intervention (PCI) as a treatment of coronary artery disease can be a simple, rapid procedure with a clear benefit for the patient, but it could also become a complex procedure with fatal consequences. These complications depend on the lesion itself, material used and also on operating staff. In this case we report a coronary artery dissection of the circumflex (CX) artery caused by inflation of an oversized balloon. We discuss here the management and evolution of this complication.